(untitled) (Journal of Social Sciences Review, 2022)
The current research study investigates the impact of ownership structure, and board composition on earnings management for a sample of 200 Pakistan Stock Exchange (PSX) listed non-financial firms. An index of ownership structure and board composition is created using Principal Component Analysis (PCA). Earnings Management is calculated using the Real Earnings Management approach. The impact of ownership structure and board composition on earnings management is investigated using the generalized method of moments (GMM). The findings of the study indicate that an increase in the levels of institutional and family ownership (ownership structure) helps in restraining the opportunistic behavior of management from managing earnings and vice versa. Conversely, board composition has a positive and noteworthy impact on earnings management. The findings of this research are useful for corporate managers in understanding the importance of ownership structure and earnings management to restrict earnings management.